All-chemical YBa2Cu3O7−δ coated conductors with preformed BaHfO3 and BaZrO3 nanocrystals on Ni5W technical substrate at the industrial scale. (20th September 2021) - Díez-Sierra, Javier; Rijckaert, Hannes; Rikel, Mark; Hänisch, Jens; Sadewasser, Mario; Koliotassis, Lisa; Meledin, Alexander; López-Domínguez, Pedro; Falter, Martina; Bennewitz, Jan; Bäcker, Michael; Driessche, Isabel Van
Abstract: We report a successful fabrication of long-length rolling-assisted biaxially-textured substrate-based coated conductors (CCs) via chemical solution deposition starting from colloidal YBa2 Cu3 O7- δ (YBCO) solutions containing 5 mol-% preformed Ba M O3 ( M = Hf, Zr) (B M O) nanocrystals. Partial optimization of the existing continuous reel-to-reel YBCO processing via design of experiments approach allowed us to obtain YBCO nanocomposites that retain 80%–90% self-field performance of the pristine CC and show a 10%–40% improvement of in-field critical current, which is only a moderate performance improvement compared to similar films on single-crystal substrates prepared on lab-scale. Based on x-ray diffraction and transmission electron microscopy studies, we attribute this to worsening of the YBCO texture and strong coarsening of B M O nanoparticles, particularly, BaZrO3, during processing. Possible process improvements to overcome these effects are discussed.